3D simulation of boreal forests: structure and dynamics in complex terrain and in a changing climate. (21st October 2015) - Brazhnik, Ksenia; Shugart, Herman H
Abstract: To understand how the Siberian boreal forests may respond to near-future climate change, we employed a modeling approach and examined thresholds for significant and irreversible changes in forest structure and composition that are likely to be reached by mid-21st century. We applied the new spatially-explicit gap-dynamics model SIBBORK toward the understanding of how transition zones, namely treelines, which are notoriously undersampled and difficult to model, may change in the near future. We found that a 2 °C change in annual average air temperature significantly altered the structure, composition, and productivity of boreal forests stands both in the northern and the southern treeline ecotones. Treeline migration occurs at smaller temperature changes. Based on the current (1990–2014) observed warming trends, a 2 °C increase in annual average temperature compared to historical climate (1961–1990) is likely to be experienced at the northern treeline by 2040 and at the southern treeline by 2050. With regards to the forest biome, the most significant warming to date has been predicted and observed in Siberia. A 2 °C increase in annual average temperature compared to the second half of the 19th century is smaller than the predictions of even the most conservative RCP2.6 climate change scenario (IPCC 2013), and has previously been assumed to not likely result in dramatic changes to ecosystems or biome shifts. We show that at a +2 °C change, biome shifts from forest to steppe are likely to occur across a large area in southern Siberia. These changes in land cover will inevitably result in changes in the biodiversity, carbon storage, and the ecosystem services provided by the boreal forests of southern Siberia.